2018
DOI: 10.5114/pjr.2018.81156
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in locally advanced rectal cancer: quantitative evaluation of the complete response to neoadjuvant therapy

Abstract: PurposeTo assess the diagnostic performance of diffusion-weighted imaging (DWI) for the discrimination of complete responder (CR) from the non-complete responder (n-CR) in patients with locally advanced rectal cancer (LARC) undergoing chemotherapy and radiation (CRT).Material and methodsBetween December 2009 and January 2014, 32 patients (33 lesions: one patient had two synchronous lesions) were enrolled in this retrospective study. All patients underwent a pre- and post-CRT conventional MRI study completed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Study characteristics and methodological details are shown in Tables 1 and 2 and Supplemental Tables 4–10 (Supplemental material available online). Combined, 19 studies investigated T2-mrTRG (2543), 39 studies investigated DW-MRI (25,32,37,4479), 13 studies investigated PW-MRI (80…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study characteristics and methodological details are shown in Tables 1 and 2 and Supplemental Tables 4–10 (Supplemental material available online). Combined, 19 studies investigated T2-mrTRG (2543), 39 studies investigated DW-MRI (25,32,37,4479), 13 studies investigated PW-MRI (80…”
Section: Resultsmentioning
confidence: 99%
“…In total, 26 studies reported data on the diagnostic performance of DW-MRI (Supplemental Table 5) (25,37,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)64,(73)(74)(75)(76)(77)(78)(79). The studies were divided into three groups of distinctly separate imaging analysis: a qualitative diffusion group comprising data from seven studies (25,44,45,(47)(48)(49)74), a quantitative ADC post group In the qualitative diffusion group, the studies performed a visual assessment of the diffusion restriction in the tumor region after nCRT.…”
Section: Adc After Chemoradiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility that ADC may be associated with the nCRT response has been amply investigated in LARC[ 8 - 12 ]; however, significant correlations have not been found in any studies to date[ 10 ]. Inconsistencies in previous findings may be due to a lack of standardized imaging and acquisition techniques[ 5 , 11 ], but they may also be due to the fact that the ADC measurements were performed using a manually drawn region of interest (ROI) from a single slice of the ADC map, which holds limited ability to reflect the actual whole-tumor characteristics[ 13 - 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the latest advancements in MRI technology, the apparent diffusion coefficient (ADC), which is obtained from diffusion-weighted imaging (DWI), has been proposed to increase the specificity of MRI in the evaluation of treatment response after nCTR ( 6 11 ).…”
Section: Introductionmentioning
confidence: 99%